PENGARUH FAKTOR PRODUKSI TERHADAP PENDAPATAN USAHATANI JERUK BRASTAGI DI DUSUN PAUSAN, KECAMATAN PAYANGAN, KABUPATEN GIANYAR - I Made Budiasa; Nyoman Yudiarini; I Made Tamba; Ni Kadek Milasari (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The contribution of oranges of Gianyar Regency to the orange production of Bali province is around 29.36%. Orange production in Pausan village has only reached 10 tons per year, with the price of oranges ranging from Rp.4,000 to Rp.6,000 per kilogram. The combination of the use of production factors greatly determines the amount of orange commodity production that will be produced, so that the allocation of production factors more optimally. The purpose of this study is to analyze production factors that affect the income of brastagi orange farmers and analyze the amount of income of brastagi orange farmers in Pausan Village, Payangan District, Gianyar Regency. The location of the study was determined intentionally (purposive sampling), and carried out from January to March 2024. The sample in this study was determined by census method, where the entire population was made respondents totaling 35 brastagi orange farmers. The data analysis methods used in this study include analysis of Cobb-Douglas production function estimation as well as cost and revenue analysis. Data on independent and dependent variables include brastagi orange production(Y), land area(X1), seeds(X2), organic fertilizer(X3), NPK fertilizer(X4), pesticides(X5), and labor(X6). The results found that all factors of production together have an effect on income, but individually do not have a significant effect on income. Land area and pesticide factors have a negative influence on farmers income. Brastagi orange farming income in Pausan hamlet reaches Rp.91,113,517 per hectare. This income per hectare comes from revenues of Rp.115,912,442 minus farming costs of Rp.24,796,774